The structure of the psychological consequences of sexual violence and abuse against children and adolescents - Nutskova, E.V. (Psihologiâ i pravo, 2016)
The results of the joint psychiatric-psychological examination of 175 victims of child sexual abuse (CSA) are presented. A complex of methods and techniques was used, including semi-structured interview for detection of posttraumatic stress in children, inventories for quality of life and maladjustment assessment, a battery of methods applied in the forensic psychiatric-psychological expertise, statistical methods. In the framework of the clinical and psychological (non-clinical) levels psychological consequences of CSA in accordance with the psychic state of victims were revealed. 4 groups of consequences with different intensity are described: psychogenic state in form of disorder (1) and psychogenic state in form of reaction (2) (clinical level); unfavorable psychological state (3) and minimally unfavorable state (4) (psychological level). It was stated that the more severe is the victim’s psychic disturbance, from minimally unfavorable to psychic disorder, the broader is the range of psychological, personality spheres involved the bigger is the number and the intensity of symptoms of posttraumatic reactions. Psychological consequences displayed by mentally healthy victims of CSA indicate, though, their quality of life impairment. В статье изложены результаты комплексного психолого-психиатрического обследования 175 несовершеннолетних потерпевших от сексуального насилия и злоупотребления. Использовался комплекс методов, включающий полуструктурированное интервью для выявления признаков посттравматического стресса у детей, методику исследования качества жизни, карты оценки дезадаптации, совокупность методик, используемых при производстве КСППЭ, методы математической статистики и анализа данных. В зависимости от психического состояния потерпевшего были выявлены психологические последствия сексуального насилия и злоупотребления клинического и психологического уровней. Описаны 4 группы последствий, различающихся по степени выраженности: психогенное состояние в форме расстройства (1) и психогенное состояние в форме реакции (2) (клинический уровень); неблагоприятное психологическое состояние (3) и минимально неблагоприятное психологическое состояние (4) (психологический уровень). Установлено, что с утяжелением психического состояния потерпевших, от минимально неблагоприятного до психогенного состояния в виде расстройства, расширяется охваченность сфер личности, количество и выраженность признаков посттравматических реакций. Психологические последствия, демонстрируемые психически здоровыми потерпевшими, свидетельствуют о снижении качества их жизни.